Respuesta :
7(x - 3) = 4(x + 5)
7(x) - 7(3) = 4(x) + 4(5)
7x - 21 = 4x + 20
- 4x - 4x
3x - 21 = 20
+ 21 + 21
3x = 41
3 3
x = 13²/₃
9(x - 2) = 18
9(x) - 9(2) = 18
9x - 18 = 18
+ 18 + 18
9x = 36
9 9
x = 4
17x - 6 + 3x - 5 = x + 11 + 4x
17x + 3x - 6 - 5 = x + 4x + 11
21x - 11 = 5x + 11
- 5x - 5x
16x - 11 = 11
+ 11 + 11
16x = 22
16 16
x = 1³/₈
7(x) - 7(3) = 4(x) + 4(5)
7x - 21 = 4x + 20
- 4x - 4x
3x - 21 = 20
+ 21 + 21
3x = 41
3 3
x = 13²/₃
9(x - 2) = 18
9(x) - 9(2) = 18
9x - 18 = 18
+ 18 + 18
9x = 36
9 9
x = 4
17x - 6 + 3x - 5 = x + 11 + 4x
17x + 3x - 6 - 5 = x + 4x + 11
21x - 11 = 5x + 11
- 5x - 5x
16x - 11 = 11
+ 11 + 11
16x = 22
16 16
x = 1³/₈
Answer:
1. Exact Form:
x=41/3
Decimal Form:
x=
13.6
Mixed Number Form:
x=13
2/3
2. x=4
3. x = 22/15
Mixed Number Form:
x= 1 7/15
Step-by-step explanation:
i go it right and that's all that matters.